The Effect of Skim Milk Concentration on Sensory Quality and pH of Probiotic Yoghurt Added with Red Dragon Fruit (Hylocereus polyrhizus) - Asterias Hafiizha; Indira Lanti Kayaputri; Tensiska Tensiska; Nur Risma Amalia (Faculty of Animal Science Universitas Brawijaya, 2020)
Probiotic yoghurt is one of dairy products that has benefits to the human health. This research aimed to understand the effect of skim milk concentration on the sensory quality traits and pH of probiotic yoghurt added with red dragon fruit (Hylocereus polyrhizus) dices prior to the fermentation. The research method was experimental method with 4 treatments and 3 replications in a completely randomized group design. The data were analyzed using one-way analysis of variance followed by Duncan’s multiple range test at P<0.05. The treatment in this research was different addition levels of skim milk (3%, 5%, 7%, and 9%) to yoghurt. The pH, color, aroma, taste, texture, viscosity and overall acceptance were assessed. The addition of skim milk increased (P<0.05) the acceptability of flavor, texture, viscosity and overall acceptance, in which the addition of skim milk at 9% showed the highest acceptability of taste. However, different addition level of skim milk did not significantly affect pH and the acceptability of color and aroma of yoghurt. The pH of yogurt ranged from 4.06 to 4.26. In addition, the color and aroma of yogurt were in the scale of neither like or dislike, the texture was in the scale of dislike to like, taste, viscosity and overall acceptance were in the scale of dislike to neither like nor dislike. In conclusion, skim milk should be used for producing yogurt with red dragon fruit at 9% of whole milk to obtain acceptable product.